Identifikasi dan Pengendalian Bahaya : Studi Kasus SMP Negeri 1 Ratahan, Sulawesi Utara - Aditya Rivky Pratama The; I Nyoman Sutapa (Jurnal Titra, 2021)
SMP Negeri 1 Ratahan is a junior high school with 520 school members. The article discusses the potential hazards related to the safety and health of the school environment. After being identified, the hazards potential with moderate to high risk rating are carried out by designing controls to reduce the risk of hazards occuring. The results of the hazard potential identification indicated that there were 4 potential hazards with medium rating and required a control design. The control design is carried out by applying the standards set by the government regulations related to school environment facilities and infrastructure and administration of school environmental health. The control design is carried out to reduce the frecuency of occurence of potential hazards and their impact.